Pemanfaatan Teknologi Penginderaan Jauh untuk Analisis Urban Heat Island di Kecamatan Sirimau Ambon - Resti Limehuwey; Sitti Hafsa Kotarumalos; Warni Multi; Micky Kololu; Philipus Josepus Patty; Robert Hutagalung (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Urban Heat Island (UHI) is a phenomenon of increasing temperature in urban areas influenced by reduced vegetation and increasing surface temperature. This study aims to analyze vegetation distribution, land surface temperature, and UHI intensity in Sirimau District using Landsat imagery from 2019 and 2022. The analysis was conducted using the Normalized Difference Vegetation Index (NDVI), Land Surface Temperature (LST), and Urban Heat Island (UHI) parameters. The results showed that NDVI values in 2019 ranged from −0.0127 to 0.8531, while in 2022 they ranged from −0.017 to 0.8309. Low NDVI values were generally found in the urban center, whereas high NDVI values were identified in areas with dense vegetation. LST values in 2019 ranged from 18.524 °C to 28.546 °C, while in 2022 they ranged from 15.359 °C to 25.382 °C. Higher surface temperatures were concentrated in urban and settlement areas, while lower temperatures were found in vegetated areas. UHI values in 2019 ranged from −1.946 °C to 2.555 °C, while in 2022 they ranged from −2.489 °C to 2.942 °C. The study indicates an inverse relationship between NDVI, LST, and UHI, where areas with low vegetation density tend to have higher surface temperatures and stronger UHI intensity compared to vegetated areas. These findings highlight the important role of vegetation in reducing surface temperature and mitigating UHI effects. The results of this study are expected to support sustainable urban planning, the development of green open spaces, and climate adaptation strategies in Sirimau District.